ChemInform Abstract: Efficient One‐Pot Synthesis of 3, 7‐Disubstituted 1, 6‐Naphthyridin‐2(1H)‐ones Through Regioselective Palladium‐Catalyzed Cross‐Coupling and SNAr Reactions. Issue 37 (September 2015) - Montoir, David; Tonnerre, Alain; Duflos, Muriel; Bazin, Marc‐Antoine
Abstract A regioselective microwave‐assisted one‐pot two‐step transformation of 1, 6‐naphthyridin‐2(1H)‐ones consisting of a Buchwald—Hartwig cross‐coupling in position 3 in the first step and a second Buchwald—Hartwig coupling, a Suzuki coupling, or a SNAr reaction in the second step is elaborated.